1998
DOI: 10.1055/s-2007-996037
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Markers of Hemostasis Activation in Obstetrics/Gynecology and Pediatrics

Abstract: Pregnancy and puerperium are considered to be hypercoagulable states with increased incidence of thromboembolic events. During normal pregnancy, changes in the hemostatic mechanism involve increased stasis and increased coagulation factors and/or decreased levels of anticoagulant proteins such as protein C and protein S as well as enhanced thrombin generation and decreased fibrinolytic activity. The physiological or pathophysiological activation of hemostasis during pregnancy results in the generation of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…This result supports the finding that both coagulation [23] and fibrinolysis [18] are activated during labor. In the study of Dati et al [24], all the markers of haemostasis activation were shown to be increased in the first 24 hr of healthy neonates. As TAFI is activated by thrombin, high levels of TAFIa may also indicate hypercoagulation.…”
Section: Discussionmentioning
confidence: 92%
“…This result supports the finding that both coagulation [23] and fibrinolysis [18] are activated during labor. In the study of Dati et al [24], all the markers of haemostasis activation were shown to be increased in the first 24 hr of healthy neonates. As TAFI is activated by thrombin, high levels of TAFIa may also indicate hypercoagulation.…”
Section: Discussionmentioning
confidence: 92%
“…As a novel anti-coagulation factor, the role of α 1 -AT in the regulation of physiological coagulation has been highlighted in the past several years. Recent studies show that α 1 -AT can bind to the activated protein C (APC) and inhibit the anticoagulation of APC [14]. In addition, α 1 -AT is also an inhibitor of coagulation factor XIa.…”
Section: Discussionmentioning
confidence: 99%
“…11 12 In pre-eclampsia, activation of coagulation, and fibrinolytic and platelet systems may alter the haemostatic balance at birth and predispose to intravascular coagulation. 13 The aims of our study were to determine the levels of the coagulation factors in premature infants at birth, and to assess the effects of gestational age and prenatal and perinatal events on the coagulation status.…”
mentioning
confidence: 99%